Vertical Cooperative Advertising in Supply Chain Management - Aust, Gerhard (Springer, 2015)
In this book methods from Operations Research and Game Theory are used to determine companies’ profit-maximizing strategies related to pricing and (cooperative) advertising. It considers different supply chain structures as well as various distributions of power, making it possible to analyze both inter-echelon and intra-echelon dependencies between the companies’ decisions. Additionally, an approach based on fuzzy set theory is presented in order to compensate for incomplete or missing data on market characteristics. Vertical cooperative advertising is an essential element of partnerships between manufacturers and retailers, allowing manufacturers to financially support their retailers’ advertising efforts so as to increase sales for the entire supply chain. Given that such programs not only make up a considerable part of many companies’ advertising budgets, but are also a controversial subject in many business relations, their correct design is of particular importance.